Health Information Search to Deal with the Exploding Amount of Health Information Produced - Müller, H.; Hanbury, A.; Al Shorbaji, N. (Methods of Information in Medicine, 2012)
Objectives: This focus theme deals with the various aspects of health information search that are necessary to cope with the challenges of an increasing amount and complexity of medical information currently produced.Methods: This editorial reviews the main challenges of health information search and summarizes the five papers of this focus theme.Results and Conclusions: The five papers of the focus theme cover a large part of the current challenges in health information search such as coding standards, information extraction from complex data, user requirements analysis, multimedia data analysis and the access to big data. Several future challenges are identified such as the combination of visual and textual data for information search and the difficulty to scale when analyzing big data.
Keywords: Health information search; information retrieval; knowledge bases; terminologies